SnS2 / ZnO nanoflower as well as preparation method and application thereof

By loading ZnO on SnS2 nanoflowers with ALD technology, SnS2/ZnO heterogas-sensitive materials are constructed, and the problems of poor complexity and reproducibility of preparation of heterogas-sensitive materials in the prior art are solved, and the high sensitivity NO2 detection performance is achieved, and it is suitable for industrial production.

CN119528210APending Publication Date: 2025-02-28QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734723.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art has problems such as complex preparation process, poor reproducibility, solvent residue, difficulty in mass production, and uncontrollable deposition of guest bodies when preparing heterogas-sensitive materials. In addition, sulphide-oxide heterojunction is easily caused by sulfide-oxide heterojunction, which destroys the heterojunction structure.

Method used

SnS2/ZnO nanoflowers were prepared by atomic layer deposition technology (ALD), and SnS2 nanoflowers were synthesized by hydrothermal technology, and then ZnO was loaded on its surface by ALD technology to construct the SnS2/ZnO heterojunction. ALD technology allows adjustment of heterogeneous layer thickness within the nanometer range, finely control electronic characteristics, and has good repeatability and controllability.

Benefits of technology

The high sensitivity detection of SnS2/ZnO nanoflower heterojunction material on NO2 has been achieved, and the response is significantly improved, the response speed and recovery time have been improved. It is suitable for industrial scale production and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528210A_ABST
    Figure CN119528210A_ABST
Patent Text Reader

Abstract

The invention discloses SnS2 / ZnO nanoflowers as well as a preparation method and application thereof, and belongs to the technical field of gas sensing materials. According to the technical scheme, the preparation method comprises the following steps: 1) respectively dissolving tin chloride and thiourea into polyethylene glycol and deionized water, stirring, transferring the solution into a reaction kettle, carrying out hydrothermal reaction, cooling, washing and drying to obtain SnS2 nanoflowers; and 2) placing the SnS2 nanoflower in an ALD reaction chamber, and depositing ZnO on the SnS2 nanoflower by multiple ALD cycles to obtain the ZnO-loaded SnS2 nanoflower. According to the preparation method, the SnS2 / ZnO nanoflower is prepared by using an atomic layer deposition (ALD) technology, and the SnS2 / ZnO heterojunction is constructed, the method is based on an ALD surface self-limiting reaction, uniform nano materials are allowed to be deposited on a large area, and high-response sensors are allowed to be produced on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas sensing materials, and specifically relates to a SnS2 / ZnO nanoflower and a preparation method and application thereof. Background Art

[0002] NO2 is one of the main air pollutants facing modern society. It has a wide range of sources and poses a serious threat to human health and the environment. Short-term exposure can cause symptoms such as coughing, wheezing, and difficulty breathing. Long-term exposure may increase the risk of respiratory infections and aggravate asthma and chronic obstructive pulmonary disease. Secondly, NO2 is one of the main precursors of acid rain. It will form acid rain when dissolved in rainwater, and it will also participate in the formation of ozone and other photochemical oxidants, exacerbating urban haze and affecting the atmosphere, water bodies, soil and ecosystems. Therefore, accurate and timely detection of NO2 gas is very important for creating a healthy and safe environment.

[0003] SnS2 (layered chalcogenide) nanomaterials have excellent electron transport properties and chemical stability, which can improve the sensitivity and selectivity of gas sensors. Sulfur atoms are naturally abundant and environmentally friendly. In addition, the relatively strong temperature dependence of the electronic band structure of SnS2 can be used to enhance the sensing response and recovery dynamics in a moderately elevated temperature range. However, the performance of a single material is often difficult to meet the needs of practical applications, especially under room temperature working conditions. In order to overcome this limitation, and considering the trade-off between low power consumption and high performance, heterojunction materials have been widely used in gas sensors because of their optimizable electronic structure. When two materials contact to form a heterojunction, electrons and holes will spontaneously transfer until the Fermi level equilibrium is reached. This process leads to the formation of charge accumulation regions and depletion regions on both sides of the heterojunction interface, thereby regulating the conductive properties of the material. At the same time, new defect states and surface states will be generated at the heterojunction interface, which can serve as active adsorption sites for gas molecules. Therefore, the construction of a heterojunction structure not only provides abundant gas adsorption sites, but also forms an efficient electron transmission channel, which is conducive to improving gas sensing performance. However, the route of preparing heterojunctions based on the solution method has limitations, including complex preparation process, poor reproducibility, solvent residue, difficulty in large-scale production, and uncontrollable deposition objects. Secondly, it is also difficult to construct sulfide-oxide heterojunctions using solvothermal technology. When growing oxides directly on the surface of sulfides, conventional operations require high-temperature calcination, and this process can easily cause oxidation reactions of sulfides, thereby destroying the desired heterojunction structure. On the contrary, if the growth order is adjusted, the oxide is grown first and then the sulfide is grown, the sulfide will often completely cover the generated oxide during the growth process. This will hinder the normal function of the oxide in the heterojunction system, prevent the oxide from exchanging charges with the outside world, and is not conducive to the separation and transmission of carriers. Summary of the invention

[0004] The present invention provides a SnS2 / ZnO nanoflower and a preparation method and application thereof. The SnS2 / ZnO nanoflower is prepared by atomic layer deposition technology (ALD) to construct a SnS2 / ZnO heterojunction. This method is based on the ALD surface self-limiting reaction, allowing uniform deposition of nanomaterials over a large area and large-scale production of high-response sensors. More importantly, the ALD technology allows the thickness of the heterolayer to be adjusted within the nanometer range by simply changing the number of ALD cycles, so that the electronic properties at the heterojunction can be finely controlled, with good repeatability and controllability. The present invention can be processed in batches and is suitable for industrial-scale production; it is environmentally friendly and uses an environmentally friendly precursor process, which improves material utilization efficiency and reduces waste.

[0005] The technical solution of the present invention is: In the first aspect, a method for preparing SnS2 / ZnO nanoflowers is disclosed, comprising the following steps: 1) Dissolve tin chloride and thiourea in polyethylene glycol and deionized water respectively to obtain tin chloride solution and thiourea solution, stir, transfer the tin chloride solution and thiourea solution to a reaction kettle, carry out hydrothermal reaction under sealing conditions, cool, wash and dry to obtain SnS2 nanoflowers; 2) placing the SnS2 nanoflowers in an ALD reaction chamber, and performing multiple ALD cycles to deposit ZnO on the SnS2 nanoflowers, thereby obtaining SnS2 nanoflowers loaded with ZnO; The ALD cycle uses diethylzinc as the Zn precursor, H2O as the oxidant, and high-purity N2 as the carrier purge gas.

[0006] Preferably, in step 1), the mass ratio of tin chloride to thiourea is (0.45-0.55): (0.65-0.75).

[0007] Preferably, in step 1), the hydrothermal reaction temperature is 180-200° C., and the reaction time is 12-16 h.

[0008] Preferably, in step 1), the cooling is performed by natural cooling to room temperature, the washing is performed by deionized water and ethanol, and the drying is performed by vacuum drying at 80-100° C. for 12 h.

[0009] Preferably, in step 2), the temperature of the reaction chamber is set to 150-180° C., the evaporation temperature of diethyl zinc is 25-45° C., and the evaporation temperature of water is room temperature.

[0010] Preferably, each ALD cycle step in step 2) comprises: a 0.02 s diethyl zinc pulse, 8 s exposure, 25 s N2 purge, 0.1 s H2O pulse, 8 s exposure, and 25 s N2 purge.

[0011] Preferably, the number of ALD cycles in step 2) is 30 to 60.

[0012] In the second aspect, SnS2 / ZnO nanoflowers prepared by the preparation method are disclosed.

[0013] In the third aspect, the application of the SnS2 / ZnO nanoflowers in NO2 detection is disclosed.

[0014] In a fourth aspect, a NO2 detection sensor is disclosed, wherein the SnS2 / ZnO nanoflowers are coated on electrodes.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention firstly adopts hydrothermal technology to synthesize SnS2 nanoflowers, and then uses diethyl zinc as zinc source to load ZnO on SnS2 nanoflowers through atomic layer deposition technology (ALD) to prepare SnS2 / ZnO nanoflower heterojunction gas-sensitive materials; ALD is a self-limiting surface reaction deposition technology that can efficiently and accurately deposit uniform and high-quality thin films on the surface of semiconductors.

[0016] 2. The special SnS2 nanoflowers prepared in the present invention have a large specific surface area and can provide abundant active sites for nitrogen dioxide adsorption, which is beneficial to improving the gas-sensitive performance of the material to nitrogen dioxide.

[0017] 3. Compared with the traditional solution method for preparing heterojunctions, the present invention has a simple and easy operation process, a clear and controllable interface, a uniform and dense deposited film, and high repeatability. It is suitable for batch preparation of gas sensors and provides a technical basis for the subsequent preparation of gas sensing nanomaterials and micro-device processing.

[0018] 4. Compared with the intrinsic SnS2 gas-sensitive material, the SnS2 / ZnO nanoflower heterojunction material prepared by the present invention has a greatly improved gas-sensitive effect on nitrogen dioxide, with a high responsiveness, up to 54 for 5ppm nitrogen dioxide, and significantly improved response speed and recovery time. The ALD technology demonstrated by the present invention shows unique advantages in heterojunction preparation, providing a new way to explore new heterojunction materials based on SnS2. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of the SnS2 / ZnO nanoflowers prepared in Example 1.

[0020] Figure 2 This is a high-magnification transmission electron microscope photograph of the SnS2 / ZnO nanoflowers prepared in Example 1.

[0021] Figure 3 This is a scanning electron microscope image of the distribution of S, Sn and Zn elements of the SnS2 / ZnO nanoflower prepared in Example 1.

[0022] Figure 4 This is the response curve of the SnS2 nanoflowers prepared in Comparative Example 1 to 5 ppm nitrogen dioxide gas at 90°C.

[0023] Figure 5 This is the response curve of the gas sensor prepared by using SnS2 / ZnO obtained by ALD cyclic deposition of 30c ZnO in Example 2 to 5ppm nitrogen dioxide gas at 90°C.

[0024] Figure 6 This is the response curve of the gas sensor prepared by using SnS2 / ZnO obtained by ALD cyclic deposition of 40c ZnO in Example 1 to 5ppm nitrogen dioxide gas at 90°C.

[0025] Figure 7 This is the response curve of the gas sensor prepared by using SnS2 / ZnO obtained by ALD cyclic deposition of 50c ZnO in Example 3 to 5ppm nitrogen dioxide gas at 90°C.

[0026] Figure 8 This is the response curve of the gas sensor prepared by using SnS2 / ZnO obtained by ALD cyclic deposition of 60c ZnO in Example 4 to 5ppm nitrogen dioxide gas at 90°C.

[0027] Fig. 9 This is a concentration gradient diagram of a gas sensor prepared using SnS2 / ZnO obtained by ALD cyclic deposition of 40c ZnO in Example 1 for 5 ppm nitrogen dioxide gas at 90°C.

[0028] Fig.10 This is a repeatability test curve of a gas sensor prepared using SnS2 / ZnO obtained by ALD cyclic deposition of 40c ZnO in Example 1 for 5 ppm nitrogen dioxide gas at 90°C.

[0029] Fig.11 This is a diagram of the interdigital electrodes used in the NO2 gas sensor used in Examples 1-4 of the present invention and Comparative Example 1.

[0030] Fig.12 This is the response curve of the gas sensor prepared by TiO2 / ZnO obtained by ALD cyclic deposition of 40c TiO2 in Comparative Example 2 to 5ppm nitrogen dioxide gas at 90°C. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0032] Example 1 The method for preparing SnS2 / ZnO nanoflowers of the present invention comprises the following steps: 1) 0.457 g of thiourea and 0.701 g of SnCl4·5H2O were added to 20 mL of polyethylene glycol 400 and 40 mL of deionized water, respectively. The mixture was stirred to obtain tin chloride solution and thiourea solution. The solution was poured into a 100 mL Teflon-lined autoclave, heated in an oven at 180 °C for 15 h, and then cooled to room temperature. The precipitate was washed with ethanol and deionized water, and then dried in a vacuum oven at 80 °C for 12 h to obtain yellow SnS2 nanoflowers.

[0033] 2) Place the SnS2 nanoflowers in the ALD reaction chamber. The ALD cycle uses diethyl zinc as the precursor of Zn, H2O as the oxidant, and high-purity N2 as the carrier purge gas. ZnO is deposited on the SnS2 nanoflowers through 40 ALD cycles to obtain SnS2 / ZnO nanoflowers. The ALD reaction chamber temperature is 150°C, and the evaporation temperatures of diethyl zinc and water are both 30°C. Each ALD cycle step includes: 0.02s diethyl zinc pulse, 8s exposure, 25s N2 purge, 0.1s H2O pulse, 8s exposure, and 25s N2 purge.

[0034] The scanning electron microscope image, high-power transmission electron microscope image, and the distribution surface scanning image of the S, Sn, and Zn elements corresponding to the scanning electron microscope of the SnS2 / ZnO nanoflower prepared in this embodiment are shown in Figures 1 and 2. Figure 1 , 2 and 3. From Figure 1 It can be observed that SnS2 / ZnO nanoflowers form SnS2 nanoflower-like structures. Figure 2 It can be clearly seen that the lattice spacing of SnS2 nanoparticles is 0.29nm, corresponding to the SnS2 (002) crystal plane, and the lattice spacing of ZnO nanoparticles is 0.24nm, corresponding to the SnS2 (101) crystal plane. Figure 3 It can be seen that the S, Sn and Zn elements are evenly distributed in the nanoflowers.

[0035] Example 2 The difference between Example 2 and Example 1 is that the number of ALD cycles in step 2) is 30 times.

[0036] Example 3 The difference between Example 3 and Example 1 is that the number of ALD cycles in step 2) is 50 times.

[0037] Example 4 The difference between Example 4 and Example 1 is that the number of ALD cycles in step 2) is 60 times.

[0038] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the SnS2 nanoflowers obtained in step (1) are not treated in step 2).

[0039] Comparative Example 2 The preparation method of SnS2 nanoflowers deposited with TiO2 in this comparative example 2 comprises the following steps: (1) The preparation of SnS2 nanoflowers is the same as step (1) of Example 1; (2) The SnS2 nanoflowers were placed in an ALD reaction chamber. The ALD cycle used titanium tetraisopropoxide as a precursor of Ti, H2O as an oxidant, and high-purity N2 as a carrier purge gas. TiO2 was deposited on the SnS2 nanoflowers through 40 ALD cycles to obtain SnS2 / TiO2 nanoflowers. The ALD reaction chamber temperature was 150°C, and the evaporation temperature of titanium tetraisopropoxide was 80°C. Each ALD cycle step included: 1s of titanium tetraisopropoxide pulse, 8s of exposure, 25s of N2 purge, 0.1s of H2O pulse, 8s of exposure, and 25s of N2 purge.

[0040] Preparation and performance test of NO2 gas sensor The NO2 gas sensor consists of three parts: glass substrate, electrode, and material sensing layer. The preparation of the NO2 gas sensor includes the following steps: (1) The geometric shape of the interdigital electrodes is controlled by a mask, and the interdigital electrodes are evaporated on a glass substrate using a high vacuum resistance evaporation coating device.

[0041] First, the glass substrate was ultrasonically cleaned with acetone and ethanol for 20 minutes to remove organic pollutants and residual acetone, and then dried with nitrogen to obtain a clean glass substrate. After that, the glass substrate was closely attached to the mask and placed in a thermal evaporation device. 10nm of Cr was deposited on the glass substrate at a rate of 5Å / s to improve the adhesion between the gold layer and the glass substrate. 30nm of Au was deposited at the same rate to form a conductive layer. Finally, an 8mm×8mm interdigital electrode was prepared. The interdigital electrode diagram is shown in the figure. Fig.11 shown.

[0042] (2) The pretreated glass substrate was cut into a 12 mm × 12 mm square, and a highly conductive silver paste was used as a connecting material to connect the two electrodes of the interdigital electrodes to the pre-prepared silver wires, and then placed in a 60°C constant temperature oven for stable drying for 1 h. 2 mg of the product sample powder prepared in Examples 1-4 and Comparative Examples 1-2 were taken and mixed with an appropriate amount of anhydrous ethanol to obtain a sensitive material suspension, and the prepared sensitive material suspension was evenly dripped onto the surface of the interdigital electrodes with a pipette for deposition, and the device with the deposited sensitive layer was placed in a constant temperature oven again for 1-2 h, thus obtaining 6 groups of NO2 gas sensors for testing.

[0043] (3) The prepared 6 groups of NO2 gas sensors were installed on a test bench equipped with a heating ceramic sheet and placed in a closed gas chamber with a volume of 6L. The test system consists of a Keithley 2401 digital source meter and a gas chamber. The static test method is used to record the resistance change of the sensor, and air is used as the control gas. The operating temperature of the sensor is controlled by adjusting the voltage across the resistor wire inside the ceramic sheet. When the sensor resistance reaches a stable state, a micro-syringe is used to inject a specific amount of NO2 gas into the gas chamber to form a NO2 atmosphere of a predetermined concentration in the gas chamber. After the resistance signal stabilizes again, the gas chamber is opened to expose it to the atmospheric environment until the sensor baseline returns to the initial state, and then the next concentration gradient test is carried out. During the entire test process, the change of resistance with concentration is continuously recorded by the signal acquisition device to obtain the dynamic response curve of the device.

[0044] Figure 4-8 The NO2 gas sensors prepared by the products of Comparative Example 1, Example 2, Example 1, Example 3 and Example 4 were respectively used to change the concentration of NO2 gas injected into the gas chamber to explore the response value of the sensor prepared by the SnS2 / ZnO nanoflowers of Example 1 as the concentration of nitrogen dioxide gas changes. Fig. 9 shown.

[0045] from Figure 4 It can be seen that the sensor made of pure SnS2 nanoflowers without ZnO loading in comparative example 1 has a response value of only 4.2 to 5ppm nitrogen dioxide gas at 90°C, and a response / recovery time of 101s / 622s. The response value is low and the recovery time is slow.

[0046] from Figure 5 It can be seen that the sensor made of SnS2 / ZnO nanoflowers with a 30cALD cycle in Example 2 has a response of 26.6 to 5ppm nitrogen dioxide at 90°C, and a response / recovery time of 90s / 232s. It has sensitive nitrogen dioxide detection performance and a significantly improved response recovery rate.

[0047] from Figure 6It can be seen that the sensor made of SnS2 / ZnO nanoflowers with 40cALD cycles in Example 1 has a response of up to 54 to 5ppm nitrogen dioxide at 90°C, and a response / recovery time of 87s / 166s. It has sensitive nitrogen dioxide detection performance and a significantly improved response recovery rate.

[0048] from Figure 7 It can be seen that the sensor made of SnS2 / ZnO nanoflowers with a 50cALD cycle in Example 3 has a response of 28.9 to 5ppm nitrogen dioxide at 90°C, and a response / recovery time of 91s / 228s. It has sensitive nitrogen dioxide detection performance and a significantly improved response recovery rate.

[0049] from Figure 8 It can be seen that the sensor made of SnS2 / ZnO nanoflowers with a 60cALD cycle in Example 4 has a response of 20.1 to 5ppm nitrogen dioxide at 90°C, and a response / recovery time of 72s / 266s. It has sensitive nitrogen dioxide detection performance and a significantly improved response recovery rate.

[0050] from Fig. 9 It can be seen that the response value of the nitrogen dioxide gas sensor in Example 1 varies linearly with the concentration of the nitrogen dioxide gas, and quantitative detection of nitrogen dioxide can be achieved.

[0051] The sensor prepared by the SnS2 / ZnO nanoflowers of Example 1 was used to investigate the repeatability of the sensor to nitrogen dioxide. The specific method was as follows: the concentration of nitrogen dioxide injected into the gas chamber was kept constant, and the sensor prepared by the SnS2 / ZnO nanoflowers of Example 1 was tested for five cycles.

[0052] from Fig.10 It can be seen from the repeatability curve of the gas sensor to nitrogen dioxide in Example 1 that the high response still has very excellent repeatability.

[0053] Fig.11 This is a real picture of the interdigital electrodes used in the nitrogen dioxide gas sensors of Examples 1-4 and Comparative Examples 1-2 of the present invention; from Fig.12 It can be seen that the sensor made of TiO2 / ZnO nanoflowers with 40 cycles of ALD in Comparative Example 2 has a response of 2.8 to 5 ppm nitrogen dioxide at 90°C, a response time of 91 s, and the response cannot be fully recovered. Compared with deposited ZnO, the performance of the gas sensor is not much improved.

[0054] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing SnS2 / ZnO nanoflowers, characterized in that: The following steps are involved: 1) Dissolve tin chloride and thiourea in polyethylene glycol and deionized water respectively, stir to obtain tin chloride solution and thiourea solution, transfer the tin chloride solution and thiourea solution to a reaction kettle, carry out hydrothermal reaction under sealing conditions, cool, wash and dry to obtain SnS2 nanoflowers; 2) Place the SnS2 nanoflowers in the ALD reaction chamber, and deposit ZnO on the SnS2 nanoflowers through multiple ALD cycles to obtain SnS2 / ZnO nanoflowers; The ALD cycle uses diethylzinc as the Zn precursor, H2O as the oxidant, and high-purity N2 as the carrier purge gas.

2. The method for preparing SnS2 / ZnO nanoflowers according to claim 1, characterized in that: In step 1), the mass ratio of tin chloride to thiourea is (0.45-0.55): (0.65-0.75).

3. The method for preparing SnS2 / ZnO nanoflowers according to claim 1, characterized in that: In step 1), the hydrothermal reaction temperature is 180-200° C. and the reaction time is 12-16 h.

4. The method for preparing SnS2 / ZnO nanoflowers according to claim 1, characterized in that: In step 1), the cooling is performed by natural cooling to room temperature, the washing is performed by deionized water and ethanol, and the drying is performed by vacuum drying at 80-100° C. for 12-24 hours.

5. The method for preparing SnS2 / ZnO nanoflowers according to claim 1, characterized in that: In step 2), the temperature of the reaction chamber is set to 150-180°C, the evaporation temperature of diethyl zinc is 25-45°C, and the evaporation temperature of water is room temperature.

6. The method for preparing SnS2 / ZnO nanoflowers according to claim 5, characterized in that: Each ALD cycle step in step 2) includes: 0.02 s diethyl zinc pulse, 8 s exposure, 25 s N2 purge, 0.1 s H2O pulse, 8 s exposure, and 25 s N2 purge.

7. The method for preparing SnS2 / ZnO nanoflowers according to claim 1, characterized in that: In step 2), the number of ALD cycles is 30 to 60 times.

8. A SnS2 / ZnO nanoflower prepared by the preparation method as described in any one of claims 1 to 7.

9. An application of the SnS2 / ZnO nanoflower as described in claim 8 in NO2 detection.

10. A NO2 gas detection sensor, characterized in that: The SnS2 / ZnO nanoflowers described in claim 8 are coated on the electrode.